PERAN MUSIK GEREJAWI DALAM MENINGKATKAN KEAKTIFAN JEMAAT DALAM IBADAH: STUDI SOSIOLOGIS DI GEREJA HKBP DAME RESSORT DAME - Martua Parluhutan Tamba; Riris Johanna Siagian; Michele Agnes Yenweri Barutu; Ebit Nego Butar-Butar; Quindando Simanjuntak (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
This study aims to examine the role of church music in enhancing congregational participation during worship services at the HKBP Dame Ressort Dame Church. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with the congregation and pastors, alongside observations conducted during worship services. The findings indicate that church music plays a crucial role in fostering a vibrant worship atmosphere and encouraging congregational participation in singing. Music functions not merely as an accompaniment to worship or a display of talent, but serves as a spiritual pathway that helps the congregation internalize the meaning of the Word of God, elevates spiritual fervor, and strengthens the sense of community. Furthermore, the quality of the musical ministry, rhythmic accuracy, and familiarity with the songs significantly influence the level of congregational participation. Contemporary challenges, such as the shifting interests of the younger generation and the instant convenience of modern music technology, are also discussed. Thus, church music is understood as a vital agent of social construction in enhancing congregational engagement both emotionally and communally within the context of church worship.